The Relationship Between Gender and Lower Jaw Third Molar Impaction Classification Determined Using Panoramic Radiographs - Fitri, Haria; Nismal, Harfindo; Sovira, Gita Dwi Jiwanda; Kasuma, Nila; Fitri, Citra (Dentistry Faculty, 2023)
Background: A pathological condition in which the obstruction of tooth eruption in the jaw arch is caused by no eruption path for teeth to grow within the predicted period. This condition is called dental impaction. The prevalence of impacted teeth is highest in women compared to men. The etiological factor is due to systemic, local, genetic, and ethnic factors. Objective: This study aimed to determine the relationship between sex and the classification of the third molar impaction of the lower jaw in patients of RSGM Andalas University viewed by panoramic radiography. Materials and Methods: The type of research conducted is observational analytical research with a Cross-sectional research design with purposive sampling techniques. The sample in this study was a panoramic X-ray of patients from RSGM Andalas University who met the inclusion and exclusion criteria. The number of samples is calculated using the Lemeshow formula. Based on the calculation results, the number of research samples was obtained as many as 32 X-ray photos. The data was analyzed using the chi-square test. Results: Distribution of frequency classification according to Pell Gregory based on known position that regions 38 and 48 in men and women occur most in position A and based on male class regions 38 and 48 often experience tooth impact in class II, while women often experience in class I, with a value of p 0.05. Conclusion: Based on the results of statistical tests, there is no significant relationship between sex and the classification of lower triple molar impaction seen by panoramic radiographs.